Comparing Tablets and PCs in teaching Mathematics: An attempt to improve Mathematics Competence in Early Childhood Education - Papadakis, Stamatis; Kalogiannakis, Michail; Zaranis, Nicholas (Preschool and Primary Education, 2016)
The present study investigates and compares the influence of using computers and tablets, in the development of mathematical competence in early childhood education. For the implementation of the survey, we conducted a 14 weeks intervention, which included one experimental and one control group. Children in both groups were taught Mathematics according to Greek curriculum for early childhood education in conjunction with the use either of the same educational software, which depending on the group, were running on computers or on tablets. In order to evaluate the mathematical performance of children we used the Test of Early Mathematics Ability (TEMA-3). The sample consisted of 256 children in Greece. The results showed that, teaching with tablets comparatively to teaching with computers has contributed significantly to the development of children’s mathematical ability to a greater extent. Moreover, factors such as gender and age did not seem to differentiate the development of mathematical competence of children.